Hubungan Health Locus of Control Dengan Perilaku Merokok Pada Remaja - Naila Iffah; Syarifah Faradina (Jurnal Online Psikogenesis, 2018)
Smoking for some individuals is a need that must be fulfill, although the impact of smoking behavior can be disadvantageous to health, economics and the environment. Smoking behavior in adolescents affected by fear is considered not socially good, left behind by the group, and considered immature. This study aims to see the relationship between health locus of control with smoking behavior in adolescents. This research uses quantitative method with purposive sampling technique (n = 60). There negative relationship between health locus of control with smoking behavior in adolescent. This shows the higher health locus of control will lead the lower smoking behavior in adolescents